Impulsivity in sales managers and merchants - Cuti Ruiz, Tatiana (2023)
The objective of this research was to identify the level of impulsivity in sales managers and merchandisers. The research has an explanatory scope and non-experimental cross-sectional design. The population was compase of the sales force personnel working in the 15 branches distributed in the city of Lima, Central East, North and South of the country. The following inclusion criteria were taken into account: workers who agreed to participate in the evaluation, workers who work in one of the 15 locations of the company and workers who work in the position of sales manager or merchandiser. The sample consisted of 698 workers. The instruments applied were a sociodemographic data questionnaire and the Barratt-BIS 11 Impulsivity Scale. During statistical processing, frequencies, percentages and means were applied. Thus, it could be concluded that there are medium and high levels of impulsivity, highlighting the dimensions of motor impulsivity and unplanned impulsivity.